Գաղափարի ընկալումը Աղասի Այվազյանի գեղագիտական աշխարհում - Գալստյան, Ա.
В статье подитожены вопросы восприятия идеи эстетического мира в произведениях Агаси Айвазяна. Восприятия идеи наблюдаются в контексте данного исторического периода, ту же идею причисляют с отражением времени идеологии, как социально классической, так и экономической и политической ориентации. В статье попытались с помощью образов Айвазяна подчеркнуть идею выдвижения, восприятия и интериоризация события. This article includes the questions of comprehension of the ideas of the aesthetical world in Aghasi Aivazyan's works. The idea's comprehension is observed in the context of that historical period; the material and the idea become the motive reflecting both the period's ideology's social-classic and the economical and political orientations. In this artical, through the Aivazyan's heroes is stressed the fact of the idea's promotion, perception and interiorization.
Keywords: Գրականագիտություն